Visual Art as Factor of Forming of Creative Environment of Trust in Modern Ukraine - Lishchyns’ka, Olga (Київський національний університет імені Тараса Шевченка, 2018)
The author discovers the role of visual art during Revolution of Dignity and hybrid war in Ukraine. The author also shows how artists put effort into building creative environment of social trust. In the article it is emphasized on the point that trust in society is formed by communion, which can be divided into common unity, common values, conversations, common actions and common creativity. It is also shown how the creatives have become active agents of creating creative environment of social trust in support of the military, doctors, volunteers, and immigrants of nowadays. The author shows that artistic processing of the subject of historic heroes, dialogue of cultural ages, appealing to key personas of our culture has a good effect on community solidarity, also has powerful uniting and integrating power in time of war. Author is raising question of artists taking part in charity events for injured, which also has positive action on uniting social trust.Keywords: Visual Art, Trust, Euromaidan, Hybrid War, Dialogue, Common Creativity.

Ольга ЛіщинськаВисвітлено роль візуального мистецтва під час Революції Гідності та гібридної війни в Україні. Розглянуто, як зусиллями митців твориться креативний простір суспільної довіри. Підкреслено, що довіра в суспільстві формується через спільність, елементами якої є спів-єдність, спів-цінності, спілкування, спів-дія, співтворчість. Розглянуто, як у сучасних умовах митці стали активними агентами творення простору суспільної довіри задля підтримки військових, медиків, волонтерів і вимушених переселенців. Показано, що мистецьке опрацювання теми історичних героїв, діалог культурних епох, звернення до знакових постатей нашої культури сприяє солідаризації громади, має потужну об’єднавчу, консолідуючу, інтегративну силу в умовах війни. Порушене питання участі митців у благодійних акціях для допомоги пораненим і постраждалим у війні, що своєю чергою скріплює суспільну довіру.Ключові слова: візуальне мистецтво, довіра, Євромайдан, гібридна війна, співтворчість, діалог.
Візуальне мистецтво як чинник формування креативного простору довіри в сучасній Україні